Analysis of Factors Influencing Budgetary Slack on Provincial Government of Jakarta, Indonesia - Lely Indriaty; Gen Norman Thomas; Hendra Railis; Yan Irianis; Mery Wanialisa (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the factors affecting budgetary slack, namely, budget participation, budget emphasis, and organizational commitment. Research Methodology: This study uses a quantitative method, and selected samples were chosen based on certain criteria, namely 10 Satuan Kerja Pemerintah Daerah (SKPDs) are the largest part of Satuan Kerja Pemerintah Daerah (SKPD) of the Provincial Government of Jakarta, Indonesia. There were 80 respondents from 43 SKPDs. Smart PLS ver.4.0 was used to test validity, reliability, and hypothesis testing. Results: The study outcomes show that budget participation and organizational commitment have significant positive effects on budgetary slack. Conclusions: All results of this study provide benefits and advantages for the Provincial Government of Jakarta in preparing provincial revenue and expenditure budgets for future years, especially since Jakarta is no longer planned as the Capital of the Republic of Indonesia. Limitations: The study uses a narrow sample of employees, sometimes focusing only on middle-level managers or specific SKPD, which might not represent the entire organization's behavior at Provincial Government of Jakarta, Indonesia Contributions: This study proves that budget participation in SKPD has potential budgetary slack if it is not balanced with high SKPD commitment but can be managed by reducing excessive budget emphasis.